2015
DOI: 10.1021/acs.jafc.5b01157
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of the Bioactive Peptide Carnosine during in Vitro Digestion of Cured Beef Meat

Abstract: A bioactive compound is a food component that may have an impact on health. Its bioaccessibility, defined as the fraction released from the food matrix into the gastrointestinal tract during digestion, depends on compound stability, interactions with other food components, and supramolecular organization of food. In this study, the effect of pH on the bioaccessibility of the bioactive dipeptide carnosine was evaluated in two commercial samples of the Italian cured beef meat bresaola at two key points of digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…The DPPH • scavenging activity of MP and SP before digestion/hydrolysis may be connected with the presence of natural antioxidant peptides in muscle tissue, i.e. glutathione, carnosine, anserine and ophidine . Furthermore, the salmon muscle tissue may contain many different components with antioxidant capacity, such as free amino acids, enzymes, hormones, carotenoids, vitamins C and E, coenzyme Q, and elements such as zinc, manganese, selenium and copper which might be extracted with salmon protein fractions and affect DPPH scavenging activity of samples before digestion/hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DPPH • scavenging activity of MP and SP before digestion/hydrolysis may be connected with the presence of natural antioxidant peptides in muscle tissue, i.e. glutathione, carnosine, anserine and ophidine . Furthermore, the salmon muscle tissue may contain many different components with antioxidant capacity, such as free amino acids, enzymes, hormones, carotenoids, vitamins C and E, coenzyme Q, and elements such as zinc, manganese, selenium and copper which might be extracted with salmon protein fractions and affect DPPH scavenging activity of samples before digestion/hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…glutathione, carnosine, anserine and ophidine. 36,37 Furthermore, the salmon muscle tissue may contain many different components with antioxidant capacity, such as free amino acids, enzymes, hormones, carotenoids, vitamins C and E, coenzyme Q, and elements such as zinc, manganese, selenium and copper which might be extracted with salmon protein fractions 38 and affect DPPH scavenging activity of samples before digestion/hydrolysis. In contrast, the antioxidant activity of salmon proteins determined with the ABTS +• scavenging method increased during digestion/hydrolysis (Fig.…”
Section: The Antioxidant Activity Of Digests and Hydrolysates Of Salmmentioning
confidence: 99%
“…Bioactive compounds must be released from the food matrix to exert a positive action and their bioaccessibility, i.e. the percentage that is made available for absorption during digestion, is influenced by many different factors including the food matrix and the food processing Ferranti et al, 2014;Marcolini et al, 2015). We hypothesize that the interactions between matrices (including DOP enrichment) and processing differently modulated bioactive bioaccessibility in conventional and experimental breads.…”
Section: Discussionmentioning
confidence: 99%
“…The discriminant analysis of the data by PLS revealed that only nine peptides were responsible for the discrimination of the cheese samples. In another application, Marcolini et al., investigated the bioaccessibility of carnosine during in vitro digestion of beef meat . Carnosine is a bioactive peptide which can act as antioxidant, antiglycating or as wound‐healing promoter.…”
Section: Peptides and Proteinsmentioning
confidence: 99%